-6(2x+3)=4x-2

Simple and best practice solution for -6(2x+3)=4x-2 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -6(2x+3)=4x-2 equation:


Simplifying
-6(2x + 3) = 4x + -2

Reorder the terms:
-6(3 + 2x) = 4x + -2
(3 * -6 + 2x * -6) = 4x + -2
(-18 + -12x) = 4x + -2

Reorder the terms:
-18 + -12x = -2 + 4x

Solving
-18 + -12x = -2 + 4x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-4x' to each side of the equation.
-18 + -12x + -4x = -2 + 4x + -4x

Combine like terms: -12x + -4x = -16x
-18 + -16x = -2 + 4x + -4x

Combine like terms: 4x + -4x = 0
-18 + -16x = -2 + 0
-18 + -16x = -2

Add '18' to each side of the equation.
-18 + 18 + -16x = -2 + 18

Combine like terms: -18 + 18 = 0
0 + -16x = -2 + 18
-16x = -2 + 18

Combine like terms: -2 + 18 = 16
-16x = 16

Divide each side by '-16'.
x = -1

Simplifying
x = -1

See similar equations:

| n/(-6)=12 | | (3x+4y)(2x+5y)= | | 24x+4y=320 | | 4=4n+12 | | sec(x)=-2.2 | | -3h+5=2h+5 | | 5p=6n | | y^2-80y+600=0 | | S+18.99+5=45 | | 24=x^2+2x | | -8(8b+2)=-8(b-5) | | 2(23)-20.8= | | 20-2(Q+9-Q)=2(9-Q) | | (3+x)x=54 | | 3x^2+6x+3+20(x+1)-7=0 | | 7m+8-5m=8+2m | | a+6a=96 | | -3x=5x-2 | | 120x+200=800 | | -39-7x=-5(3x-5) | | 15t=5(5t+1) | | 7x+8=379 | | 75y^4-3X^4=0 | | -10a=8a | | -6(4n+5)-4=-202 | | 194-w=83 | | 8x+56=1x+16 | | M-4=28 | | 4d+8c=8.8 | | 20-2(Q+P)=2 | | (3x-6)+(4x-9)=90 | | 3(a-6)=4a+9-a |

Equations solver categories